A dataset of primary nasopharyngeal carcinoma MRI with multi-modalities segmentation - Yin Li; Qi Chen; Meige Li; Liping Si; Yingwei Guo; Yu Xiong; Qixing Wang; Yang Qin; Ling Xu; Patrick van der Smagt; Kai Wang; Jun Tang; et al. (Scientific Data)
Abstract Multi-modality magnetic resonance imaging(MRI) data facilitate the early diagnosis, tumor segmentation, and disease staging in the management of nasopharyngeal carcinoma (NPC). The lack of publicly available, comprehensive datasets limits advancements in diagnosis, treatment planning, and the development of machine learning algorithms for NPC. Addressing this critical need, we introduce the first comprehensive NPC MRI dataset, encompassing MR axial imaging of 277 primary NPC patients. This dataset includes T1-weighted, T2-weighted, and contrast-enhanced T1-weighted sequences, totaling 831 scans. In addition to the corresponding clinical data, manually annotated and labeled segmentations by experienced radiologists offer high-quality data resources from untreated primary NPC.